ACCOUNTING FOR NO-PAR STOCKS DURING THE DEPRESSION. - Hornberger, D. J. (The Accounting Review, 1933)
Abstract Accounting for no-par stock issues during the years 1930-1932, where changes have been made in the methods of stating capital stock valuations in those years, presents several most interesting contrasts with the period 1921-1929. During the past three years business conditions have been, for most corporations, just the reverse of the period prior to 1929, and these reversals in financial conditions are being rapidly reflected in the changing methods of accounting for no-par issues, capital surplus, earned surplus and related accounts, as of March 1933. In the period prior to 1929, the par-value security was rapidly giving way before the newer and so-called advantageous no-par security. Properties were being appraised, the added value was credited to some surplus or no-par stock account, and the sum total used as an excuse to make stock split-ups, carry stock values at the net worth without a differentiation between types or sources, and so on. Where in 1918-1929 corporation valuations went wild in one direction today undoubtedly they are going wild in the other.